Mutations in domain V of the 23S ribosomal RNA of Bacillus subtilis that inactivate its protein folding property in vitro - Chowdhury, Saheli (Oxford University Press, 2002)
The active site of a protein folding reaction is in domain V of the 23S rRNA in the bacterial ribosome and its homologs in other organisms. This domain has long been known as the peptidyl transferase center. Domain V of Bacillus subtilis is split into two segments, the more conserved large peptidyl transferase loop (RNA1) and the rest (RNA2). These two segments together act as a protein folding modulator as well as the complete domain V RNA. A number of site-directed mutations were introduced in RNA1 and RNA2 of B.subtilis, taking clues from reports of these sites being involved in various steps of protein synthesis. For example, sites like G2505, U2506, U2584 and U2585 in Escherichia coli RNA1 region are protected by deacylated tRNA at high Mg(2+) concentration and A2602 is protected by amino acyl tRNA when the P site remains occupied already. Mutations A2058G and A2059G in the RNA1 region render the ribosome Ery(r) in E.coli and Lnc(r) in tobacco chloroplast. Sites in P loop G2252 and G2253 in E.coli are protected against modification by the CCA end of the P site bound tRNA. Mutations were introduced in corresponding nucleotides in B.subtilis RNA1 and RNA2 of domain V. The mutants were tested for refolding using unfolded protein binding assays with unfolded carbonic anhydrase. In the protein folding assay, the mutants showed partial to complete loss of this activity. In the filter binding assay for the RNA–refolding protein complex, the mutants showed an extent of protein binding that agreed well with their protein folding activity.